2015
DOI: 10.1089/sur.2014.028
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Shampoo Effects in Neurosurgical Patients: A Pilot Experimental Study

Abstract: In our pilot study, the results of which are not generalizable because of the limited sample of patients involved, a gentle shampoo offered 72 h after the surgical procedure did not increase the SSIs occurrence or the contamination of the surgical site, although it may increase the perception of comfort by patients. Further studies are strongly recommended involving a larger sample size and designed to include more diversified neurosurgical patients undergoing surgical procedures in different centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Five studies (6% of included studies) focused on SSI prevention as the primary outcome, using a variety of interventions: postoperative shampooing; 66 preoperative 2% chlorhexidine gluconate skin preparation cloths; 42 silver impregnated versus standard dry sterile dressings (cardiac surgery): 26 hair shaving techniques; 61 different antiseptic methods. 88 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (6% of included studies) focused on SSI prevention as the primary outcome, using a variety of interventions: postoperative shampooing; 66 preoperative 2% chlorhexidine gluconate skin preparation cloths; 42 silver impregnated versus standard dry sterile dressings (cardiac surgery): 26 hair shaving techniques; 61 different antiseptic methods. 88 …”
Section: Resultsmentioning
confidence: 99%
“…34,35,42,56,61,76,85,96 Almost half of the included studies assessed outcomes at multiple phases of the perioperative pathway (n = 34, 40%), whilst 24 studies (28%) assessed postoperative outcomes extending beyond the immediate PACU phase. 26,27,34,35,39,40,41,43,45,48,51,55,61,62,64,66,69,73,89,90,92,99,102,109 Five studies (6%) assessed outcomes only during the preoperative phase, 57,58,71,103,106 whilst only four studies assessed outcomes at a single phase of intraoperative care (n=4, 6%), 33,46,56,59,74 and seven studies assessed outcomes during PACU care only (n=7, 8%). 24,44,47,68,82,100,…”
Section: Phases Of Carementioning
confidence: 99%
“…This rate was reported between 1–9% after cranial surgery (Sebastian , Palese et al . ). Type of surgery, use of implant, duration of surgery and presence of cerebrospinal fluid fistula may affect the rate of SSI after surgery (Sneh‐Arbib et al .…”
Section: Introductionmentioning
confidence: 97%
“…It is widely accepted that hair shaving is an important factor affecting body image, which is one of the basic components of personality (Doğan , Palese et al . ). Hair is an important part of human physical appearance and plays an important role in the workings of social status and communication (Ratanalert & Srıplung ).…”
Section: Introductionmentioning
confidence: 97%
“…Early hair washing improved personal hygiene and helped minimize the time needed to return to normal life. Palese et al [27] reported that shampoo offered 72 h after surgery did not increase the SSI rate, but did increase patient comfort.…”
Section: Benefits Of Early Shampooingmentioning
confidence: 99%